Impact of COVID-19 on health-related behaviours, well-being and weight management - Amanda Avery; Josef Toon; Jennifer Kent; Laura Holloway; Jacquie Lavin; Sarah-Elizabeth Bennett (BMC, 2021)
Abstract Background Weight management is complex for people even in times of stability. Supporting individuals to develop strategies to maintain a healthier weight when there are additional life challenges may prevent relapse. This mixed-methods study describes the impact the COVID-19 restrictions had on adults engaged in weight management before and during the pandemic in order to determine helpful strategies. Methods Longitudinal data was captured from online surveys completed by Slimming World (SW) members 0-4 weeks after joining, October/November 2019, providing pre-joining and baseline (T0&T1), 3- (T2) and 6- month (T3-during COVID-19) data. Representatives from the general population, not attending a weight management service, completed the same questionnaires providing cross-sectional control data. All weights are self-reported. For this study, questions assessing the impact of the COVID-19 challenges on health-related behaviours and well-being are included comparing responses at T0/T1, T2 & T3. Longitudinal data were analysed using repeated measures ANOVA and cross-sectional data, one-way independent ANOVAs to compare means. Comparisons between SW members and controls were determined using z-proportion tests. Qualitative data generated was thematically analysed using a six-step approach to produce the key emerging themes. Results 222 SW members completed all three surveys, achieving a weight loss of 7.7 ± 7.5%. They maintained positive health-related behaviour changes made since joining, including increased fruit and vegetables (p < 0.001), fewer sugary drinks (p < 0.001), cooking from scratch (p < 0.001) and increased activity levels (p < 0.001). Despite COVID-19 restrictions, they were still reporting improvements in all behaviours and had healthier scores than the controls on all but alcohol intake, although still within guidelines. Qualitative data indicated that the situation created various challenges to managing weight with fresh foods harder to access, comfort eating, drinking more alcohol, eating more sugary foods and snacking through boredom. However, some reported having more free time enabling better planning, more time to cook from scratch and increased physical activity. Conclusions The findings highlight the value of peer, group and online support and guidance for individuals to develop sustainable behaviour changes and a level of resilience. These strategies can then be drawn upon enabling maintenance of lifestyle changes and management of weight even in challenging times.